2017
DOI: 10.1016/j.exer.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Rho GTPase/Rho kinase signaling pathway in pathogenesis and treatment of glaucoma: Bench to bedside research

Abstract: Glaucoma is a leading cause of irreversible blindness worldwide. Elevated intraocular pressure (IOP) is considered to be a predominant risk factor for primary open angle glaucoma, the most prevalent form of glaucoma. Although the etiological mechanisms responsible for increased IOP are not completely clear, impairment in aqueous humor (AH) drainage through the conventional or trabecular pathway is recognized to be a primary cause in glaucoma patients. Importantly, lowering of IOP has been demonstrated to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
183
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(193 citation statements)
references
References 149 publications
9
183
0
1
Order By: Relevance
“…Excessive actin polymerization, αSMA-dependent contractility and ECM upregulation represent key harbingers of increased outflow resistance in glaucoma (86,87). Indicating that mechanotransduction contributes to use-dependent formation, alignment and plasticity of cell contacts, we found that exposure to Yoda1 suffices for the upregulation of stress fibers and vinculin-containing puncta.…”
Section: Discussionmentioning
confidence: 63%
“…Excessive actin polymerization, αSMA-dependent contractility and ECM upregulation represent key harbingers of increased outflow resistance in glaucoma (86,87). Indicating that mechanotransduction contributes to use-dependent formation, alignment and plasticity of cell contacts, we found that exposure to Yoda1 suffices for the upregulation of stress fibers and vinculin-containing puncta.…”
Section: Discussionmentioning
confidence: 63%
“…However, this AE may be intolerable to some patients and, in the current study, led to discontinuation in 4.0% of netarsudil-treated patients. Although conjunctival hyperemia is an expected consequence of the known vasodilatory effects of ROCK inhibition, [23][24][25] this ocular AE is not specific to ROCK inhibitors. In a meta-analysis of randomized clinical trials of…”
Section: In the Phase 3 Rocket-4 Study Netarsudilmentioning
confidence: 99%
“…Based on this mechanism of action, the drug is expected to be more effective in POAG than PACG. ROCK inhibition reduces cell contractility and cell stiffness, and it decreases expression of fibrosis‐related proteins, resulting in increased trabecular outflow facility . In addition, netarsudil has norepinephrine transporter (NET) inhibitory activity, which may be responsible for the documented reduction of aqueous humor production and decrease in episcleral venous pressure, thereby further contributing to the lowering of IOP .…”
Section: Optimization Of Iop‐lowering Medical Treatmentmentioning
confidence: 99%
“…ROCK inhibition reduces cell contractility and cell stiffness, and it decreases expression of fibrosis-related proteins, resulting in increased trabecular outflow facility. [29][30][31] In addition, netarsudil has norepinephrine transporter (NET) inhibitory activity, which may be responsible for the documented reduction of aqueous humor production and decrease in episcleral venous pressure, thereby further contributing to the lowering of IOP. 29,32,33 Testing of netarsudil 0.02% ophthalmic solution (corresponding to commercial Rhopressa™) resulted in IOP reduction of ~5 mm Hg in normal Dutch Belted rabbits and Formosan Rock monkeys, but there are no published reports on its effectiveness in dogs.…”
Section: Lowering Medical Treatmentmentioning
confidence: 99%